A consistent anisotropic damage model for laminated fiber-reinforced composites using the 3D-version of the Puck failure criterion. (November 2017) - Reinoso, J.; Catalanotti, G.; Blázquez, A.; Areias, P.; Camanho, P.P.; París, F.
Abstract: This paper presents a consistent anisotropic damage model for laminated fiber-reinforced composites relying on the 3D-version of the Puck failure criterion. The current model is based on ply failure mechanisms (fiber and inter-fiber failures) incorporating energetic considerations into the progressive damage evolution. The proposed formulation is implemented into the implicit FE commercial package ABAQUS using the user-defined capabilityUMAT . Additionally, the current damage model is combined with a locking-free solid shell formulation via the user-defined subroutineUEL in order to account for geometrical nonlinear effects in thin-walled applications. The reliability of the current formulation is first examined by means of several benchmark applications, and subsequently, the obtained numerical predictions are compared with experimental data corresponding to an open hole tension test. These applications show the practicability and accuracy of the proposed methodology for triggering damage in composite laminates, providing a robust modeling framework suitable for general specimens and loading conditions.